Neodymium isotopic composition and rare earth element concentration in the deep and intermediate Nordic Seas: constraints on the Iceland Scotland Overflow Water signature - Lacan, F.; Jeandel, C. (Geochemistry, Geophysics, Geosystems, 2004)
International audience Neodymium isotopic composition and rare earth element concentrations were measured in seawater samples from eleven stations in the Nordic Seas. These data allow us to study how the Iceland Scotland Overflow Water (ISOW) acquires its neodymium signature in the modern ocean. The waters overflowing the Faroe Shetland channel are characterized by ɛNd = −8.2 ± 0.6, in good agreement with the only other data point, published 19 years ago. In the Greenland and Iceland Seas the water masses leading to the formation of the ISOW display lower neodymium isotopic composition, with ɛNd around −11 and −9, respectively. Since no water masses in the Nordic Seas are characterized by ɛNd > −8, the radiogenic signature of the ISOW likely reflects inputs from the highly radiogenic Norwegian Basin basaltic margins (Jan-Mayen, Iceland, Faroe, with ɛNd ≈ +7). In addition to the neodymium isotopic composition, the rare earth element patterns suggest that these inputs occur via the remobilization (which includes resuspension and dissolution) of sediments deposited on the margins. Whereas the neodymium isotopic composition behaves conservatively in the oceans in the absence of lithogenic inputs, and can be used as a water mass tracer, these results emphasize the role of interactions, between sediments deposited on margins and seawater, in the acquisition of the neodymium isotopic composition of water masses. These results should allow a better use of this parameter to trace the present and the past circulation in the North Atlantic.